The fox and the crane - N/A (Delhi My kids world)
The fox invited the crane to dinner and served soup in a shallow dish, which the crane couldn$1 (Bt eat. Later, the crane invited the fox and served food in a tall jar, which the fox couldn$1 (Bt eat. Moral: Treat others the way you want to be treated.s
Keywords: English